2015
DOI: 10.2196/jmir.3951
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mHealth Chronic Disease Management on Treatment Adherence and Patient Outcomes: A Systematic Review

Abstract: BackgroundAdherence to chronic disease management is critical to achieving improved health outcomes, quality of life, and cost-effective health care. As the burden of chronic diseases continues to grow globally, so does the impact of non-adherence. Mobile technologies are increasingly being used in health care and public health practice (mHealth) for patient communication, monitoring, and education, and to facilitate adherence to chronic diseases management.ObjectiveWe conducted a systematic review of the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
732
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 997 publications
(813 citation statements)
references
References 79 publications
20
732
0
13
Order By: Relevance
“…In recent years, many projects and programs have been initiated with the objective to develop new models of service delivery, capitalizing on the potential of telehealth to improve accessibility, quality, continuity, efficiency and integration of health care and services, especially for populations with chronic diseases and those living in rural and remote areas [2,[4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many projects and programs have been initiated with the objective to develop new models of service delivery, capitalizing on the potential of telehealth to improve accessibility, quality, continuity, efficiency and integration of health care and services, especially for populations with chronic diseases and those living in rural and remote areas [2,[4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…There are many factors that could contribute to the success of the innovations, some being experience of the health care workers providing care to the patients, increased adherence due to other factors like fear of death due to unusual or change of circumstances, media campaigns and the messages being relayed through those mobile devices. Based on their popularity, availability, portability, and technological capacity, mobile phones have enormous potential to impact chronic disease management around the globe [7]. Mobile technologies such as phones and wireless monitoring devices are increasingly being used in health care and public health practice for communication, data collection, patient monitoring, and education, and to facilitate adherence to chronic disease management.…”
Section: Introductionmentioning
confidence: 99%
“…[1] More than half of the adults in the U.S. have at least one chronic condition (e.g., hypertension, coronary heart disease, stroke, diabetes, and cancer). [2,3]Cardiovascular disease (CVD) and diabetes are two common chronic conditions that share common risk factors including: age, genetic factors, obesity, poor nutrition, impaired glucose tolerance and physical inactivity.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] The need for continuous monitoring, long term planning and frequent interaction of chronic patients with their providers might be addressed with ongoing technological advancements. [1] Emerging health technologies are increasingly being used in health care for communication, data collection, patient monitoring, education, and to facilitate adherence to chronic disease management. [6,8] It has been suggested that various telehealth technologies can assist in reducing both burden and cost of CVD around the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation